2002
DOI: 10.2307/3078860
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen in Insects: Implications for Trophic Complexity and Species Diversification

Abstract: Disparities in nutrient content (nitrogen and phosphorus) between herbivores and their plant resources have lately proven to have major consequences for herbivore success, consumer-driven nutrient cycling, and the fate of primary production in ecosystems. Here we extend these findings by examining patterns of nutrient content between animals at higher trophic levels, specifically between insect herbivores and predators. Using a recently compiled database on insect nutrient content, we found that predators exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
396
9
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(430 citation statements)
references
References 0 publications
24
396
9
1
Order By: Relevance
“…In our study, the only pattern in %C was that taxa with sclerotized or armored integuments had greater mean %C than taxa with membranous integuments (Table 1). The slightly higher %N and low C:N of predators relative to other FFGs in our study also agrees with results of other studies (Fagan et al 2002, Evans-White et al 2005, Hambäck et al 2009). The %C and %N of Tabanus sp.…”
Section: Patterns Of C N and P Contentsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, the only pattern in %C was that taxa with sclerotized or armored integuments had greater mean %C than taxa with membranous integuments (Table 1). The slightly higher %N and low C:N of predators relative to other FFGs in our study also agrees with results of other studies (Fagan et al 2002, Evans-White et al 2005, Hambäck et al 2009). The %C and %N of Tabanus sp.…”
Section: Patterns Of C N and P Contentsupporting
confidence: 83%
“…Furthermore, growth rates are positively correlated with body %P (Elser et al 1996, Frost and Elser 2002, Weider et al 2005) but negatively correlated with adult invertebrate body size (Woods et al 2004). Phylogeny also may constrain P (Woods et al 2004) and N (Fagan et al 2002) content of invertebrates, independent of ontogeny.…”
mentioning
confidence: 99%
“…2000; Fagan et al. 2002). Nevertheless, the principles explored in these models could easily be extended to considerations of other important elements such as phosphorus.…”
Section: The Theoretical Frameworkmentioning
confidence: 99%
“…Fagan et al (2002) detected higher N concentrations in insect predators compared with herbivores after adjusting for allometry and phylogeny. They suggested that N contents in diets, being higher in plant-feeding insects than in plants, contribute to higher N concentrations in predators.…”
Section: Discussionmentioning
confidence: 99%